Anchoring and suspending pipe string mechanical behavior of slip ram for subsea blowout preventer. (1st March 2022) - Li, Tao; Jiang, Dapeng; Xie, Peng
Abstract: For exploring the anchoring and suspending pipe string mechanical behavior of slip ram for subsea blowout preventer is of critical importance for reliable sealing wellhead in an emergency, the wedge stress theory and thick-walled cylinder theory are applied to analysis anchoring and suspending mechanical behavior of slip ram, respectively. The stress of slip inserts is very tiny in the approaching pipe process and stress concentration occurs at the slip inserts edge when contacting pipe, while the stress of slip inserts is pre-volatile and then gradually stabilized in the suspending process; the mean stress is approximately uniform in each slip inserts at the final moment. The numerical results indicated the wedge stress theory and the thick-walled cylinder theory are applicable to analyze the anchoring stress and suspending stress (mean stress) of slip inserts respectively. The visible damage and plastic deformation occur in the slip or CT90 tube after completing the anchoring and suspending operation whether numerical or experimental results. Furthermore, the sensitive parameters research shows that the slips are damaged in the anchoring stage depends on their structural strength, while in the suspending stage depends on their structural shear strength. Highlights: The wedge stress theory and the thick-walled cylinder theory are applied to analysis anchoring and suspending mechanical behavior of slip ram, respectively. The stress and shear stress of slip ram in the numerical anchoring and suspending CT90 tube process are obtained. The damage and plastic deformation occur in the slip ram and CT90 pipe are highly consistent in numerical or experimental. The sensitive parameters of the stress and shear stress of slip were discussed in the anchoring and suspending process.